The Analysis of Well-being’s Level on Athletes with Special Needs (ACPES (ASEAN Council of Physical Education and Sport) in cooperation with Universitas Negeri Semarang (UNNES), 2022)
This is qualitative research that uses a descriptive approach focuses on knowing the level of welfare of athletes with special needs in national training centers. Primary data was obtained by using interviews addressed to 20 athletes who were willing to be resource persons. Interviews were conducted based on the welfare level instrument used by the Central Bureau of Statistics of Indonesia with indicators in the form of income, expenses, living conditions, housing facilities, ease of obtaining health services, and ease of obtaining transportation facilities. In addition, researchers also took information in the form of monthly salary receipt data obtained by athletes as secondary data from this study. The data was then analyzed using the NVivo 12 Pro. The search results using the word cloud feature in the NVivo 12 Pro application program that comes from all research data, the sentence